2020
DOI: 10.1007/s40688-020-00290-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Restorative Justice in US K-12 Schools: a Review of Quantitative Research

Abstract: This article provides an overview of restorative justice (RJ) in US K-12 schools, discusses implementation challenges, and summarizes the most recent two decades of quantitative studies regarding the effectiveness of RJ at achieving a range of outcomes. While RJ has become increasingly popular, there is still relatively little quantitative research regarding its effectiveness. Still, available evidence suggests that RJ programs can improve school climates and reduce student misbehavior and school discipline. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 32 publications
(54 reference statements)
0
25
0
11
Order By: Relevance
“…From the studies examined, results of great interest emerged regarding the benefits of applying restorative justice and practices in schools, as also confirmed by the theoretical articles and reviews reported in the Appendix A [ 57 , 58 , 59 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, there is still limited evidence in terms of direct correlation, which suggests further studies.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…From the studies examined, results of great interest emerged regarding the benefits of applying restorative justice and practices in schools, as also confirmed by the theoretical articles and reviews reported in the Appendix A [ 57 , 58 , 59 , 60 , 61 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. However, there is still limited evidence in terms of direct correlation, which suggests further studies.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, some studies showed better academic performance, resulting in lower levels of absenteeism. In this sense, in line with the academic scientific literature, in schools that have implemented restorative justice and restorative practices, there is a slight increase in the average grade, an increase in graduation rates, and a more than double decrease in dropout rates [ 60 ]. Therefore, the implementation of the restorative approach and restorative practices is expressed not only as a response to conflict, but in a preventive key to welcome and care for people, relationships, communities.…”
Section: Discussionmentioning
confidence: 89%
“…Implementing PBIS may require educators to not only implement Recognition systems, but also directly address racially driven cognitive barriers to students’ trust (Yeager et al, 2014, 2017) and educators’ cognitive biases of lowered expectations (Downey & Pribesh, 2004; Tenenbaum & Ruck, 2007). The empirical evidence for relationship-oriented practices (e.g., trust-building, restorative discipline) remains sparse (Darling-Hammond et al, 2020) and should be evaluated in the context of PBIS implementation. Furthermore, research is needed to examine the experiences of Latinx students related to trusting student–teacher relationships.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches have successfully been applied in school settings through the use of talking circles and community‐based intergenerational art projects (Berman & Hassinger, 2012; Shein, 2021), which have in turn increased participants’ ownership of the process, led to interruption of the school‐to‐prison pipeline, improvement of relationships, and prevention of destructive ways of engaging conflict, fostering meaningful dialog and increasing academic and social achievements (Ortega et al., 2016). Although their effectiveness in preventing bullying has been found to be equivocal, they have been found to reduce misbehavior and the need for disciplining (Darling‐Hammond et al., 2020). Moreover, these interventions have enabled students, parents, and teachers to find ways of giving voice to community concerns while working together to strengthen communication and esprit du corps (Shein, 2021).…”
Section: Summary and New Directionsmentioning
confidence: 99%